STRONG \(n\)-CONVEX \(n\)-NORMED SPACES - Malčeski, Risto (Matematichki Bilten, 1997)
The concept of a \(n\)-skalar product on a vector space of dimension greater than \(n-1\) and \(n\)-norm, introduced by A. Misiak ([6]), is a multidimensional analog of the scalar product and the norm. In [6] and [5] are proved the basic properties of a \(n\)-preHilbert and \(n\)-normed space. In this work we will give a generalisation and some properties of a strong 2-convex 2-normed spaces which was treat in [2] and [3].